ESTIMATION OF MINERALS AND HEAVY METALS ON AERIAL PARTS OF PHYLLANTHUS LONGIFLORUS - JESUPILLAI, M; ARASU, P THILLAI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The objective of the present study was to quantify minerals and heavy metals present in aerial parts of Phyllanthus longiflorus (PHL). Essential elements such as sodium (Na), potassium (K), iron (Fe), magnesium (Mg), zinc (Zn) and non essential elements such copper (Co), lead (Pb), cadmium (Cd), manganese (Mn) and mercury (Hg) were estimated using atomic absorption spectroscopy. Results show that minerals such as Fe, Na and Mg are present in the concentration of 343.9820, 537.7724 and117.2173 ppm respectively. Heavy metals such as Co, Cd and Pb was present in the concentration of 15.6916, 1.8899 and 0.3591ppm respectively. Also the result revealed that the absence (not detectable) of potassium, manganese, mercury and zinc in the aerial parts of PHL. Therefore, the data provided in the present study could be useful in the preparation of standard herbal products of this plant.